Three essays on economic impact assessment of the use of the Heavily Indebted Poor Countries (HIPC) initiative for poverty reduction in Ghana - Osei-Fosu, Anthony Kofi (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of the Degree of Doctor of Philosophy in Economics